Taxation of special investment contracts participants - R. A. Shepenko; A. G. Isaev (Правоприменение)
16. Balandina A.S. Analysis of theoretical aspects of tax benefits and tax preferences. Vestnik Tomskogo gosudarstvenogo universiteta = Tomsk State University Journal, 2011, no. 4 (16), pp. 105–110. (In Russ.). 17. Danilova V.V. Tax preferences: the concept, types, goals and procedures for obtaining. Oplata truda: bukhgalterskii uchet i nalogooblozhenie, 2022, no. 4, pp. 19–26. (In Russ.). 18. Wells D.A. The Theory and Practice of Taxation. New York, D. Appleton and Company Publ., 1900. 666 p. 19. Chua A.T. Precedent and Principles of WTO Panel Jurisprudence. Berkeley Journal of International Law, 1998, vol. 16, iss. 2, pp. 171–196. 20. Belousov A.L. Preferential regimes for conduct of business: regulation problems and law improvement areas. Khozyaistvo i pravo = Economy and Law, 2022, no. 10, pp. 30–41. (In Russ.). 21. Belousov A.L. Legal aspects of formation and development of special investment contracts in the Russian Federation. Legal Bulletin, 2022, vol. 7, no. 4, pp. 9–16. (In Russ).The subject. The preferential tax regime provided to the participants of special investment contracts has been functioning in the Russian legal system for about 8 years. Despite the systematic "fine-tuning" of its legal regulation, taxpayers still face the legislative gaps and contradictions of separate normative provisions entailing tax risks. It seems appropriate to put forward the hypothesis that the existing tax treatment of the participants of special investment contracts is not devoid of these drawbacks, especially in terms of regional regulation, and could be improved. Purpose of the study. The article represents an attempt to verify the aforementioned hypothesis and deals with selected provisions of the Russian legislation regulating preferential tax regime for participants of special investment contracts, which in addition to the Russian Tax Code includes the Federal Law "On Industrial Policy in the Russian Federation", regional and municipal normative legal acts. Methodology. The methodological basis of this study are general scientific methods (analysis and synthesis, induction and deduction), private scientific methods (interpretation of legal acts), as well as content analysis, study of reports and analytical references of governmental organizations. The main results. The study revealed that the Russian legislation, mainly regional and municipal, is not fully developed. As a consequence, the preferential tax regime for the participants of special investment contracts cannot efficiently function on the entire Russian territory. Also, the regulatory framework adopted at the federal level uses incorrect terminological apparatus in terms of defining tax support measures available to participants of special investment contracts, which entails tax risks for them. Conclusions. The revealed drawbacks of the preferential tax regime for participants of special investment contracts can be leveled by means of point-by-point amendments to the federal legislation. To this end, the authors of the present study propose specific steps to overcome these drawbacks.